Rental Land Fund of Treasury in Siberia in Early 20th Century - V. I. Panteleev; I. I. Voronov (Научный диалог)
The structure of the rental land fund of the Treasury in Siberia at the beginning of the 20th century is considered. The relevance of the study is determined by the need for effective use of the Russian Federation state lands at present stage. In this regard, it is useful to refer to the experience gained during the agrarian reforms of the early 20th century. Special attention is paid to Siberia as the main region of colonization in the years of Stolypin agrarian reform. The influence of departmental ownership of the rental fund of the Treasury on the efficiency of its operation is shown. The rental land fund of the Department of State Land Property and Forest Department is considered in detail. The methods of state land lease and their tenants are analyzed. Data from archival sources are entered into scientific circulation. It is proved that the profitability of the exploited state-owned land fund has grown under the influence of the colonization flow in the years of Stolypin agrarian reform. The authors argue that the government’s resettlement policy primarily influenced the increase in the profitability of the land fund leased by the state. It is emphasized that the search for land for immigrants during the reform was a priority, even despite the risk of damage to particularly valuable forests.